2014
DOI: 10.3945/jn.113.184663
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Pharmacokinetics of Novel Alkylresorcinol Metabolites in Human Urine, New Candidate Biomarkers for Whole-Grain Wheat and Rye Intake

Abstract: Biomarkers of dietary intake are prominent tools in nutritional research. The alkylresorcinol metabolites 3,5-dihydroxybenzoic acid (3,5-DHBA) and 3-(3,5-dihydroxyphenyl)propanoic acid (3,5-DHPPA) have been proposed as exposure biomarkers of whole-grain (WG) wheat and rye intake. However, the profile of alkylresorcinol metabolites is not fully understood. The aim of this study was to investigate the metabolism of alkylresorcinols in mice and in humans, while further determining urinary pharmacokinetics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 37 publications
8
54
0
Order By: Relevance
“…So far, no study has reported the presence of these novel metabolites in urine after rye consumption, and it is possible that the urinary AR metabolite composition differ after wheat and rye intake. This is supported by the DHPPA/DHBA ratio in urine which is usually >2 after wheat-based AR intake as reported here and elsewhere [9,25], while the ratio in studies where rye is the primary AR source commonly <2 after rye-based AR consumption [16,17,33,34]. Unlike previous studies [16,17], no inverse relationship between AR intake and urinary AR metabolite recovery was observed.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…So far, no study has reported the presence of these novel metabolites in urine after rye consumption, and it is possible that the urinary AR metabolite composition differ after wheat and rye intake. This is supported by the DHPPA/DHBA ratio in urine which is usually >2 after wheat-based AR intake as reported here and elsewhere [9,25], while the ratio in studies where rye is the primary AR source commonly <2 after rye-based AR consumption [16,17,33,34]. Unlike previous studies [16,17], no inverse relationship between AR intake and urinary AR metabolite recovery was observed.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, two novel AR metabolites [5-(3,5-dihydroxyphenyl)-pentanoic acid and 2-(3,5-dihydroxybenzamido)-acetic acid] were recently detected in human urine after a single dose of WG wheat bread and accounted for ~12 % of all AR metabolites in urine [9]. So far, no study has reported the presence of these novel metabolites in urine after rye consumption, and it is possible that the urinary AR metabolite composition differ after wheat and rye intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A slightly modified protocol based on a previous method [21] was developed to allow accurate quantification of four novel AR metabolites recently identified (DHPPTA, DHBA-glycine, DHCA and DHCA-amide) along with DHBA and DHPPA in urine samples [17,18]. Enzymatic hydrolysis, extraction and SPE of DHBA and DHPPA have been optimized previously [21], and similar conditions were applied in the present method.…”
Section: Determination Of Ar Metabolites In Urinementioning
confidence: 99%
“…These metabolites are 3-(3, 5-dihydroxyphenyl)-1-propanoic acid (DHPPA) and 3,5-dihydroxybenzoic acid (DHBA). In a recent study, 5-(3,5-dihydroxyphenyl) pentatonic acid (DHPPTA) and 2-(3,5-dihydroxybenzamido) acetic acid (DHBAglycine) were also described as urinary metabolites derived from AR [17]. Moreover, 3,5-dihydroxycinnamic acid (DHCA) and 3,5-dihydroxycinnamic acid amide (DHCA-amide) have recently been identified in urine and suggested as AR metabolites [18].…”
Section: Introductionmentioning
confidence: 95%